Surface characterization of silicon and glass for anodic bonding at room temperature using lab assembled high voltage device - Muhamad Hafiz Ab Aziz (School of Microelectronic Engineering, 2011)
The main objective of this study is to investigate high voltage anodic bonding at room temperature and determine if hermetic anodic bonding can be achieved.